IoT-based Heart Rate Variability Tracker for Music Therapy - Wan Johari, Wan Muzammil (IRC, 2019)
Music has been widely used for thousands of years for many occasions and the potential of utilizing as an established profession is only known for a short amount of time. The music therapy consisted of its two main components, receptive technique and active technique. The project is mainly focusing on receptive technique as it can be done using less equipment and without being conducted by music therapist all the time. Music therapy is not widely available in Malaysia as the awareness among societies is low and the limited number of certified music therapist. To ensure the efficacy of the Music Therapy treatment, the measurement of Heart Rate Variability of the user is one of the main factors in this project. The main goal of this project is to be able to deliver a music therapy treatment despite of the location of the user, by utilizing the Internet of Things (IoT). The project consisted of developing a hardware device which is used to measure the Heart Rate Variability of the user, which then being submitted through IoT to the mobile application for providing music therapy session using receptive technique. The results indicate that the music therapy treatment using receptive technique through mobile phone does have an impact on the user. Further research is needed to identify other factors that could increase the effectiveness of this music therapy on the go.